Vivir en tiempos convulsionados Reflexiones sociocríticas para propuestas de intervención social - Iturrieta, Sandra (Ariadna Ediciones, 2021)
There are multiple reasons why a group of people takes on the task of writing a book. In our case, "Living in troubled times: from socio-critical reflections to proposals for social intervention", which is the first book produced by the Research Center on Professions in Contemporary Societies, of the Pontifical Catholic University of Valparaíso, responds to a double interest. On the one hand, in the politically turbulent times that run in Chile and Latin America, we want to be participants in the construction of the subjectivities with which we will face the future sociocultural and political framework. In such a scenario we are interested in problematizing the crossroads, opportunities, interspaces, challenges, limits, and the borders or cracks of social intervention, from different multidimensional and interdisciplinary points of view. On the other hand, with a writing committed to socio-critical thoughts, we want to give a voice to the experiences, achievements and concerns that professionals of direct social intervention, or face to face, have related to us through various instances. His courage to challenge life in troubled times has inspired us to set as a goal, in the writing of each of the chapters, the development of proposals related to social intervention and professional training in social sciences, and in particular in Social Work .